"Privileged" under Nazi-Rule: The Fate of Three Intermarried Families in Vienna. Issue 3 (3rd July 2019) - Raggam-Blesch, Michaela
ABSTRACT: In this article, I highlight the daily life of three intermarried families in Vienna during the interwar years, the Nazi oppression and the immediate postwar period. All three families led secular lives with varying ties to their Jewish and non - Jewish environment. After the Nazi takeover in March 1938, intermarried families along with the Jewish population experienced immediate discrimination and ostracism. This paper aims to outline how the Nazi takeover affected these families in their day-to-day encounters with non - Jews as well as their relationships with friends and family members. "Mixed marriages" and their families navigated between Jewish and non-Jewish worlds, usually not fully belonging to any side. Thus, most of them experienced social isolation and a lacking sense of belonging, while others – mostly younger generations – sometimes found new forms of community. During the last years of the war their protection became more precarious and even trivial infractions against Nazi laws could lead to imprisonment and deportation. Since "mixed marriages" and their families did not officially learn about the key factors of their safeguarding, they were left to their own instincts on how to uphold their protection.